1999
DOI: 10.1016/s0092-8674(00)81524-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal to Epithelial Conversion in Rat Metanephros Is Induced by LIF

Abstract: Inductive signals cause conversion of mesenchyme into epithelia during the formation of many organs. Yet a century of study has not revealed the inducing molecules. Using a standard model of induction, we found that ureteric bud cells secrete factors that convert kidney mesenchyme to epithelia that, remarkably, then form nephrons. Purification and sequencing of one such factor identified it as leukemia inhibitory factor (LIF). LIF acted on epithelial precursors that we identified by the expression of Pax2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
171
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(176 citation statements)
references
References 64 publications
3
171
2
Order By: Relevance
“…Another question that remains is how Wnt signaling relates to the activity of other factors that appear to be sufficient for kidney tubule formation, including the leukemia inhibitory factor (Lif) and transforming growth factor beta (TGFβ) [48,49]. Previous studies have shown that, similarly to Wnt9b and Wnt4, both of these factors weakly induce canonical Wnt signaling in isolated mesenchyme.…”
Section: Wnts In Renal Vesicle Formationmentioning
confidence: 99%
“…Another question that remains is how Wnt signaling relates to the activity of other factors that appear to be sufficient for kidney tubule formation, including the leukemia inhibitory factor (Lif) and transforming growth factor beta (TGFβ) [48,49]. Previous studies have shown that, similarly to Wnt9b and Wnt4, both of these factors weakly induce canonical Wnt signaling in isolated mesenchyme.…”
Section: Wnts In Renal Vesicle Formationmentioning
confidence: 99%
“…Leukemia inhibitory factor and the associated transient activation of STAT proteins has been implicated in inducing conversion of metanephric mesenchyme/blastema to podocytes and epithelial tubules of the nephron (Barasch et al, 1999;Plisov et al, 2001). We, therefore, hypothesized that abnormal constitutive activation of STATs in metanephric mesenchyme may lead to the deregulation of the differentiation program, resulting in renal tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…LIF is a 40-45 kDa monomeric glycoprotein belonging to the IL6 family of cytokines. It is a pleiotropic molecule known to induce differentiation of mouse myeloid leukaemic cells [17], regeneration of muscle [18] and nerve [19], and mesenchymal-to-epithelial transdifferentiation in the developing kidney [20], whereas it inhibits differentiation and promotes proliferation of embryonic stem cells [21]. The action of LIF is mediated by a functional LIF receptor composed of two signal-transducing proteins, LIF receptor-β (LIFR) and gp130.…”
Section: Introductionmentioning
confidence: 99%